2017
DOI: 10.1016/j.ultrasmedbio.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Shear Wave Velocity Detection in the Porcine Heart

Abstract: Cardiac muscle stiffness can potentially be estimated non-invasively with shear wave elastography. Shear waves are present on the septal wall after mitral and aortic valve closure, thus providing an opportunity to assess stiffness in early systole and early diastole. We report on the shear wave recordings of 22 minipigs with high-frame-rate echocardiography. The waves were captured with 4000 frames/s using a programmable commercial ultrasound machine. The wave pattern was extracted from the data through a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
6
61
0
Order By: Relevance
“…The propagation velocity of the aortic valve closure wave in our healthy patients is lower than that found in a group of 10 human patients by Brekke et al (2014) (5.41 § 1.28 m/s), or in animal studies (Hollender et al 2012;Vos et al 2017). We speculate that the difference is originating from the different detection method and probe positioning: parasternal in our study in agreement with Kanai (2005) as opposed to apical in the study by Brekke et al (2014).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The propagation velocity of the aortic valve closure wave in our healthy patients is lower than that found in a group of 10 human patients by Brekke et al (2014) (5.41 § 1.28 m/s), or in animal studies (Hollender et al 2012;Vos et al 2017). We speculate that the difference is originating from the different detection method and probe positioning: parasternal in our study in agreement with Kanai (2005) as opposed to apical in the study by Brekke et al (2014).…”
Section: Discussionsupporting
confidence: 49%
“…In animal model studies, the propagation of the mitral valve shear wave has been found to be lower than the aortic (Vos et al 2017). The opposite finding in the human heart cannot be explained by differences in electromechanical activation (Konofagou and Provost 2012;Costet et al 2014).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the feasibility of noninvasive measurements of shear wave elastography, a number of studies have been performed and technical advancements are under development . It has been shown that shear wave measurements can be recorded transthoracically in human and porcine models . A number of researchers have reported feasibility of ARFI measurement transthoracically during the cardiac cycle in clinical subjects .…”
Section: Discussionmentioning
confidence: 99%
“…23 It has been shown that shear wave measurements can be recorded transthoracically in human and porcine models. 24,25 A number of researchers have reported feasibility of ARFI measurement transthoracically during the cardiac cycle in clinical subjects. 20,26 Moreover, transthoracic SWEI measurements have been demonstrated in the clinic.…”
Section: Vejdani-jahromi Et Al-intraventricular Pressure By Ultrasounmentioning
confidence: 99%